6x-2=9(x+8)

Simple and best practice solution for 6x-2=9(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2=9(x+8) equation:


Simplifying
6x + -2 = 9(x + 8)

Reorder the terms:
-2 + 6x = 9(x + 8)

Reorder the terms:
-2 + 6x = 9(8 + x)
-2 + 6x = (8 * 9 + x * 9)
-2 + 6x = (72 + 9x)

Solving
-2 + 6x = 72 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-2 + 6x + -9x = 72 + 9x + -9x

Combine like terms: 6x + -9x = -3x
-2 + -3x = 72 + 9x + -9x

Combine like terms: 9x + -9x = 0
-2 + -3x = 72 + 0
-2 + -3x = 72

Add '2' to each side of the equation.
-2 + 2 + -3x = 72 + 2

Combine like terms: -2 + 2 = 0
0 + -3x = 72 + 2
-3x = 72 + 2

Combine like terms: 72 + 2 = 74
-3x = 74

Divide each side by '-3'.
x = -24.66666667

Simplifying
x = -24.66666667

See similar equations:

| x^2-4x+12=3+2x | | 8-15n=5(-3n+2) | | 3x^2+4x=360 | | 120=.8*x | | (5+3i)(6-3i)= | | 10x+8y=4800 | | 8p-57=9p+10 | | 120=.8x | | -4x^2+29x-25=0 | | (sec^2)(x)=7 | | 47-12=5(x-2) | | x^3-3y^3-9z^3=0 | | x+3.5x=90 | | 1566=29(p+20) | | x+x+15+x+75=180 | | 14x=11x+33 | | x+18+3x=-20-3x-25 | | 14x=11x+34 | | 14x=11x+36 | | 14x=11x+41 | | 14x=11x+61 | | -1/5b-2/5=-3 | | 11x=3y-3 | | x^2-6x=135 | | 12t^2-18t+7=0 | | 14x=11x+81 | | 180=x+(2x)+(x-20) | | 23-48=3(x-1)-4 | | 10x/11 | | f(-2)=3x^2+7x-12 | | y-2=x^2-3x+7 | | B/14-b/22 |

Equations solver categories